The Effectiveness of Catheterization Pre-Action Education on the Knowledge of Coronary Heart Patients in the ICVCU Room of Prof. Dr. H. Aloei Soboe Hospital, Gorontalo City - Rahmad Lanasir; Pipin Yunus; Haslinda Damansayah (International Journal of Health, Economics, and Social Sciences (IJHESS), 2026)
Coronary Heart Disease (CHD) is a disease of the heart and blood vessels caused by narrowing of the coronary arteries. Narrowing of blood vessels occurs due to the process of atherosclerosis due to the slow accumulation of cholesterol and connective tissue on the walls of blood vessels. The research method is a research strategy in identifying problems before the final planning of data collection, the research design used in this study is Quasy Experimental using the paired t-test. From the results of the analysis, patient knowledge was obtained before the pre-catheterization education was carried out at Prof. Dr. H. Aloei Saboe Hospital. From 30 respondents, 3 respondents (10%) were obtained, they had good knowledge and as many as 27 respondents (90%) had poor knowledge. From the results of the analysis, it was found that the patient's knowledge after pre-catheterization education was obtained from 30 respondents, 29 respondents (96.7%), had good knowledge and as many as 1 respondent (3.3%) had poor knowledge. From the results of the significance test using the paired t test on the comparison of the frequency of patient knowledge before and after the Pre-action of cardiac catheterization education at Prof. Dr. H. Aloei Saboe Hospital , there was a significant change with a value of p=.001 (p<0.05), then it can be concluded that there is an Effectiveness of Pre-Catheterization Education on the Knowledge of Coronary Heart Patients in the ICVCU Room of Prof. Dr.H. Aloei Soboe Kota Hospital Gorontalo.